Implementasi Program Keahlian Bisnis Daring dan Pemasaran dalam Membentuk Karakter Wirausaha Peserta Didik Kelas XII di SMK PGRI Sumber Agung Kabupaten OKU Timur Tahun Pelajaran 2021-2022 - Arifin, Zaenal (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Online business and marketing is a skills program that prepares young people who can form an entrepreneurial character and have the ability to think creatively and innovatively in facing the global economy. The aim of the research is to determine the planning of online businessand marketing skills programs, the implementation of online business and marketing skills programs, and the obstacles to online business and marketing skills programs in forming the entrepreneurial character of class XII students at SMK PGRI Sumber Agung.This research was conducted using qualitative methods through a descriptive approach. The results of this research are (1) Implementation of the online business and marketing skills program at PGRI Sumber Agung Vocational School in shaping the entrepreneurial character of class XII students. (2) Implementation of online business and marketing skills program planning at PGRI Sumber Agung Vocational School has been well planned which includes programs, strategies and policies. (3) Implementation of online business and marketing skills programs to shape the entrepreneurial character of class XII students in the form of providing material through productive textbooks, comparative studies or visits to the business world and entrepreneurial practices. (4) The implementation obstacles faced are learning and practical facilities and students' personal obstacles.